PROGRAM FAMILY DEVELOPMENT SESSION (FDS) UNTUK MENINGKATKAN POLA ASUH ORANG TUA KPM PKH - Muhamad Ikhsan; Prita Yolandari; Dian Rosdiana (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2022)
This research aims to determine the effectiveness of the Family Devolpment Session (FDS) program to improve the parenting patterns of parents of Beneficiary Families (KPM), the Family Hope Program (PKH). This research uses a quantitative approach. The data collection method used was interview and observation methods. Data analysis uses pre-test data which is collected and processed to be used as a reference in developing the FDS program to improve the parenting patterns of KPM PKH parents. The results of testing the effectiveness of using the FDS program to improve the parenting patterns of KPM PKH parents in Serang Regency using a two-average difference test show that the use of the FDS program has proven to be effective in improving the parenting patterns of KPM PKH parents. The use of the FDS program is said to be effective because it has succeeded in improving parents' parenting patterns as a whole or in each of its components.